Osteochondral scaffold with biological energy activity and preparation method of osteochondral scaffold

By chemically reacting the intermediate of the tricarboxylic acid cycle with triol, bioenergy materials are prepared, and combined with crosslinking agents and osteogenic agents, an osteocartilage scaffold with bioenergy activity is constructed through gradient 3D printing, which solves the problems of insufficient bioenergy activity and poor interface binding ability of the osteocartilage scaffold in the prior art, and achieves efficient tissue regeneration effect.

CN119656377APending Publication Date: 2025-03-21HUAZHONG UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411862156.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing osteocartilage stents are insufficient in terms of bioenergy activity, mismatch in degradation speed, and poor interface binding ability, resulting in poor tissue regeneration effect.

Method used

By chemically reacting the intermediate of the tricarboxylic acid cycle with triol, bioenergy material prepolymer is prepared and combined with crosslinking agents and osteogenic agents, a bioenergy-active osteocartilage scaffold is constructed through gradient 3D printing, and the structure of the cartilage layer, transition layer and subchondral bone layer is simulated.

Benefits of technology

It realizes that the scaffold produces bioenergy active units during the degradation process, improves the cell energy state, accelerates tissue regeneration, and improves the interface binding ability and cell adhesion ability of the scaffold through bionic gradient structure and multi-stage pore structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119656377A_ABST
    Figure CN119656377A_ABST
Patent Text Reader

Abstract

The invention relates to an osteochondral scaffold with biological energy activity and a preparation method of the osteochondral scaffold, and belongs to the technical field of biological materials and tissue engineering. The method comprises the following steps: carrying out first chemical reaction on an intermediate of tricarboxylic acid cycle and trihydric alcohol to obtain a bio-energy material prepolymer; performing a second chemical reaction on the bio-energy material prepolymer and a cross-linking agent, and adding an osteogenesis promoting agent into a system of the second chemical reaction to obtain composite slurry; regulating and controlling the weight of the osteogenesis promoting agents in the composite slurry to obtain three biological energy material inks containing the osteogenesis promoting agents with different weights; carrying out gradient type 3D printing on the three kinds of biological energy material ink containing the osteogenesis promoting agents with different weights so as to respectively simulate a cartilage layer, a transition layer and a subchondral bone layer in the articular cartilage, and carrying out a third chemical reaction after 3D printing, so as to obtain the target osteochondral scaffold. The osteochondral scaffold provided by the invention has biological energy activity, and realizes regeneration of transparent cartilage and reconstruction of an osteochondral complex interface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of biomaterials and tissue engineering, and in particular to a bone cartilage scaffold with bioenergetic activity and a preparation method thereof. Background Art

[0002] Osteochondral defects are often caused by sports trauma, aging, and joint diseases such as osteoarthritis, which are harmful to physical health, and the joint pain caused also affects the quality of life. Tissue engineering is an emerging field that reconstructs damaged tissues or organs of the human body by combining seed cells, growth factors, and scaffolds for biomimetic design. At present, cartilage tissue engineering has attracted much attention. In order to achieve a good repair effect, the tissue engineering scaffold needs to be similar to the physiological structure of natural cartilage and have a gradient distribution of inorganic calcium and phosphorus. At the same time, the scaffold should also have a pore structure suitable for cell migration and ingrowth as well as nutrient transport, good bonding ability with surrounding tissues, and a degradation rate that matches the regeneration of new tissues. In addition, the scaffold material should also have good biocompatibility, and the material itself and its degradation products should not cause any inflammatory response or cytotoxicity.

[0003] However, in tissue engineering, scaffolds play a role in supporting cell adhesion and growth. Cartilage repair materials such as collagen, gelatin, and hyaluronic acid have excellent biocompatibility, but they degrade quickly and cannot support cartilage regeneration for a long time. Synthetic polymers such as PCL (polycaprolactone) and PLA (polylactic acid) have stable structures but slow degradation, no bioenergy activity, and poor ability to promote tissue regeneration. Summary of the invention

[0004] The present application provides a bone cartilage scaffold with bioenergetic activity and a preparation method thereof to solve the following technical problem: how to improve the bioenergetic activity of the bone cartilage scaffold.

[0005] In a first aspect, an embodiment of the present application provides a method for preparing a bone cartilage scaffold having bioenergetic activity, the method comprising:

[0006] The intermediate of tricarboxylic acid cycle is subjected to a first chemical reaction with triol to obtain a bioenergy material prepolymer;

[0007] The bioenergy material prepolymer and the cross-linking agent are subjected to a second chemical reaction, and a bone formation promoting agent is added to the system of the second chemical reaction to obtain a composite slurry;

[0008] Regulating the weight of the osteogenic agent in the composite slurry to obtain three bioenergy material inks containing different weights of the osteogenic agent;

[0009] The three bioenergy material inks containing different weights of osteogenic agents are subjected to gradient 3D printing to respectively simulate the cartilage layer, transition layer and subchondral bone layer in articular cartilage to obtain an osteochondral scaffold with bioenergetic activity.

[0010] Optionally, the intermediates of the tricarboxylic acid cycle include at least one of the following: citric acid, α-ketoglutaric acid, succinic acid, fumaric acid, malic acid, oxaloacetic acid; and / or,

[0011] The triol includes at least one of the following: glycerol, butanetriol, hexanetriol, and decantriol.

[0012] Optionally, the molar ratio of the intermediate of the tricarboxylic acid cycle to the triol is (1-3):1; and / or,

[0013] The temperature of the first chemical reaction is 120°C to 160°C.

[0014] Optionally, the bone-promoting agent includes one of the following: hydroxyapatite, tricalcium phosphate, and bioactive glass.

[0015] Optionally, the cross-linking agent includes at least one of the following: toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, and lysine diisocyanate.

[0016] Optionally, the 3D printing temperature is 60°C to 80°C.

[0017] Optionally, the second chemical reaction system further contains a pore-forming agent.

[0018] Optionally, the three bioenergy material inks containing different weights of bone-promoting agents include: a first bioenergy material ink, a second bioenergy material ink and a third bioenergy material ink; wherein,

[0019] The first bioenergy material ink satisfies: the weight ratio of the bioenergy material prepolymer to the pore-forming agent is 10:20;

[0020] The second bioenergy material ink satisfies: the weight ratio of the bioenergy material prepolymer, the pore-forming agent and the bone-promoting agent is 10:15.69:1.76;

[0021] The third bioenergy material ink satisfies: the weight ratio of the bioenergy material prepolymer, the pore-forming agent and the bone-promoting agent is 10:9.52:4.29.

[0022] Optionally, the method further includes: subjecting the osteochondrocyte scaffold to a third chemical reaction to obtain a target osteochondrocyte scaffold; wherein the process parameters of the third chemical reaction include: a temperature of 120° C. to 160° C. and a time of 24 h to 48 h.

[0023] In a second aspect, an embodiment of the present application provides a bone cartilage scaffold, and the bone cartilage scaffold is prepared by the method described in any embodiment of the first aspect.

[0024] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0025] The preparation method of the osteochondrium scaffold with bioenergetic activity provided in an embodiment of the present application comprises: subjecting an intermediate of a tricarboxylic acid cycle to a first chemical reaction with a triol to obtain a bioenergy material prepolymer; subjecting the bioenergy material prepolymer to a second chemical reaction with a cross-linking agent, and adding a bone-promoting agent to the system of the second chemical reaction to obtain a composite slurry; regulating the weight of the bone-promoting agent in the composite slurry to obtain three bioenergy material inks containing different weights of the bone-promoting agent; and performing gradient 3D printing on the three bioenergy material inks containing different weights of the bone-promoting agent to respectively simulate the cartilage layer, transition layer and subchondral bone layer in the articular cartilage to obtain a osteochondrium scaffold. The intermediates of the tricarboxylic acid cycle are synthesized with triols to form high molecular polymers, which participate in the construction of tissue engineering scaffolds; the bioenergy material prepolymer is used as a substrate, and the cross-linking agent and the osteogenic agent are fully mixed to prepare the bioenergy material-hydroxyapatite composite bio-ink, and then a three-dimensional porous scaffold is constructed by 3D printing; the scaffold can produce bioenergetic active units during the degradation process, which can be absorbed and utilized by cells to enter the mitochondrial tricarboxylic acid cycle, increase the tricarboxylic acid cycle speed by establishing a key intermediate biological bypass, and increase the production of cellular adenosine triphosphate (ATP), thereby accelerating tissue regeneration by supplying energy, reflecting the bioenergetic activity of the osteochondrocyte scaffold, achieving hyaline cartilage regeneration and reconstruction of the complex osteochondrocyte interface. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0027] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following is a brief introduction to the drawings required for use in the embodiments or the description of the prior art. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0028] Figure 1A schematic flow chart of a method for preparing a bone cartilage scaffold with bioenergetic activity provided in an embodiment of the present application;

[0029] Figure 2 The JC-1 staining results of the cells provided in the examples of the present application after being treated with the test medium;

[0030] Figure 3 The results of the mitochondrial membrane potential change and ATP activity test after the cells provided in the examples of the present application were treated with the test medium;

[0031] Figure 4 Physical pictures, SEM pictures and element distribution energy spectrum of the osteochondrium scaffold with bioenergetic activity provided in the embodiments of the present application;

[0032] Figure 5 Interlayer scanning electron microscopy images of the osteochondral scaffold and PCL scaffold with bioenergetic activity provided in the embodiments of the present application;

[0033] Figure 6 A repair diagram of an osteochondral scaffold with bioenergetic activity provided in an embodiment of the present application applied to osteochondral defect repair surgery;

[0034] Figure 7 The histological staining results of the osteochondral scaffold with bioenergetic activity provided in the examples of the present application 12 weeks after the osteochondral defect repair surgery. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0036] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0037] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present specification, the terms "including", "comprising", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of the associated objects, indicating that there may be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "plural" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of singular or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple. In the proportional relationship involved in this article, the parameters that need to be described by proportion should be understood as the first term of the proportional formula in the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, the mass ratio of substance A, substance B, and substance C is 1:2:3, then substance A, substance B, and substance C should correspond one-to-one with the proportional numbers in the proportional formula in the order of description, that is, the mass of substance A: the mass of substance B: the mass of substance C = 1:2:3.

[0038] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0039] At present, (1) the existing osteochondral scaffolds have insufficient bioactivity and poor tissue regeneration ability. In tissue engineering, scaffolds play a role in supporting cell adhesion and growth. Cartilage layer repair materials such as collagen, gelatin, and hyaluronic acid have excellent biocompatibility, but they degrade quickly and cannot support cartilage regeneration for a long time. Synthetic polymers such as PCL and PLA have stable structures but slow degradation and no bioactivity, and poor tissue regeneration ability. (2) Problems with integrated molding of osteochondral scaffolds. The osteochondral unit has a distinct layered structure. It consists of two main tissues: subchondral bone and articular cartilage. The latter can be further divided into four regions from the surface to the depth: superficial zone, middle zone, deep zone, and calcified zone. The optimal regeneration of these two tissues is almost impossible to achieve with a single material component because the two tissues have different cell states and mechanical performances. Therefore, multiple inks are often used to print and construct osteochondral scaffolds. For example, the cartilage layer often uses collagen, gelatin, hyaluronic acid, etc., and the subchondral bone layer uses hydroxyapatite, tricalcium phosphate and other materials. This type of ink is used to print the cartilage layer and the subchondral bone layer respectively, and an osteochondral scaffold is obtained by physical bonding. However, the interface bonding ability of this type of osteochondral scaffold is weak, and it is easy to crack during the repair process, resulting in ultimate repair failure. Therefore, when constructing an osteochondral scaffold, how to achieve stable interface bonding is a major difficulty. (3) Adding growth factors / seed cells and biosafety risks. Currently, tissue engineering methods often use the addition of seed cells and growth factors to scaffold materials to improve biological activity. However, this method is expensive and uncontrollable. It is specifically reflected in the loading and activity maintenance of seed cells in the scaffold material, as well as the controlled release of growth factors. Early burst release of growth factors will affect the long-term repair effect, and may even lead to risks such as ectopic osteogenesis and tumor occurrence.

[0040] Therefore, in view of the above-mentioned defects, in the first aspect, the embodiments of the present application provide a method for preparing a bone cartilage scaffold with bioenergetic activity. Figure 1 A schematic diagram of a process for preparing a bone cartilage scaffold with bioenergetic activity provided in an embodiment of the present application; see Figure 1 , the method comprising:

[0041] S1, performing a first chemical reaction on an intermediate of a tricarboxylic acid cycle and a triol to obtain a bioenergy material prepolymer;

[0042] In some embodiments, the intermediates of the tricarboxylic acid cycle include at least one of the following: citric acid, α-ketoglutaric acid, succinic acid, fumaric acid, malic acid, oxaloacetic acid; and / or,

[0043] The triol includes at least one of the following: glycerol, butanetriol, hexanetriol, and decantriol.

[0044] The tricarboxylic acid cycle (TCA cycle), also known as the citric acid cycle or Krebs cycle, is a key link in cellular aerobic respiration. It occurs in the mitochondrial matrix of eukaryotes and the cytoplasm of prokaryotes. The intermediates of the tricarboxylic acid cycle refer to a series of intermediate compounds produced in this cycle. These compounds serve as both products of the cycle and reactants of subsequent reactions, driving the cycle to continue.

[0045] In the embodiments of the present application, the tricarboxylic acid cycle itself is at the core of energy metabolism in the organism, and the intermediates involved often have unique chemical structures and active functional groups, such as groups containing carboxyl groups, carbonyl groups, etc. that can participate in polymerization reactions. The triol provides multiple hydroxyl groups, which can undergo chemical reactions such as polycondensation and esterification with the relevant functional groups on the intermediates, thereby gradually building up high molecular polymers and then participating in the construction of tissue engineering scaffolds; the scaffold releases intermediates during degradation, which can enter the cell mitochondria, participate in the tricarboxylic acid cycle, and increase the cell energy state to produce more ATP to accelerate tissue regeneration. Exemplarily, the intermediates of the tricarboxylic acid cycle can be a combination of one or more of citric acid, α-ketoglutaric acid, succinic acid, fumaric acid, malic acid, and oxaloacetic acid; the triol can be a combination of one or more of glycerol, butanetriol, hexanetriol, and decantriol.

[0046] In some embodiments, the molar ratio of the intermediate of the tricarboxylic acid cycle to the triol is (1-3):1; and / or,

[0047] The temperature of the first chemical reaction is 120°C to 160°C.

[0048] In an embodiment of the present application, the molar ratio of the intermediate of the tricarboxylic acid cycle to the triol can be (1 to 3): 1, so that the hydroxyl group of the triol and the carboxyl group on the intermediate of the tricarboxylic acid cycle are fully esterified. Exemplarily, the molar ratio of the intermediate of the tricarboxylic acid cycle to the triol can be 1: 1, 2: 1, 3: 1, etc. The temperature of the first chemical reaction can be 120°C to 160°C, and the first chemical reaction is an esterification reaction between the hydroxyl group of the triol and the carboxyl group on the intermediate of the tricarboxylic acid cycle to obtain a polymer chain. At a reaction temperature of 120°C to 160°C, the target product can be obtained to avoid the introduction of by-products. Exemplarily, the temperatures of the first chemical reaction and the second chemical reaction can be 120°C, 130°C, 140°C, 150°C, 160°C, etc.

[0049] S1 is specifically as follows: the intermediate of the tricarboxylic acid cycle and the triol are placed in an oil bath at 120°C to 160°C, and after the two monomers are completely mixed, the reaction is stirred at a vacuum degree of -80 to 95KPa for 3h to 8h to obtain a colorless, transparent, flowing bioenergy material prepolymer.

[0050] S2, subjecting the bioenergy material prepolymer to a second chemical reaction with a cross-linking agent, and adding a bone-promoting agent to the system of the second chemical reaction to obtain a composite slurry;

[0051] In some embodiments, the osteogenic agent comprises one of the following: hydroxyapatite, tricalcium phosphate, and bioactive glass.

[0052] In some embodiments, the cross-linking agent includes at least one of the following: toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, and lysine diisocyanate.

[0053] In the embodiment of the present application, the crosslinking agent increases the molecular weight of the bioenergy material prepolymer by reacting with the hydroxyl group in the bioenergy material prepolymer (one-time crosslinking). This process is like using "bonds" (chemical bonds formed by the crosslinking agent) to connect the dispersed "chains" (prepolymer molecular chains) into a larger and more complex "network structure", which helps to enhance the overall performance of the bioenergy material prepolymer, such as improving its mechanical strength and stability, making it more suitable as a basic material for tissue engineering scaffolds. And retain a large number of hydrolyzable groups, such as ester bonds, carbamate bonds, etc. On the one hand, when the scaffold is implanted in the body, as time goes by and the physiological process in the body proceeds, these hydrolyzable groups can gradually undergo hydrolysis reactions, so that the material can be degraded in a controllable and gradual manner; on the other hand, the presence of hydrolyzable groups may also be related to the function of the material releasing bioenergy active units, etc. During the hydrolysis process, it may promote the better release of active units so that they can be taken up and utilized by cells, and then participate in energy metabolism processes such as the tricarboxylic acid cycle, and help tissue regeneration.

[0054] Osteogenesis promoter is the main inorganic component of bone, with biological activity and biocompatibility; bioenergy material composite osteogenic agent will have a significant osteogenic effect; natural articular cartilage has a layered structure, which is divided into cartilage layer, transition layer and subchondral bone layer from top to bottom, wherein the weight of osteogenic agent presents a gradient increase; according to the bionic principle, bioenergy composite ink containing different weights of osteogenic agent is used to print and prepare a biomimetic gradient osteochondral scaffold with bioenergetic activity. Exemplarily, the osteogenic agent can be a combination of one or more of hydroxyapatite, tricalcium phosphate, and bioactive glass; the crosslinking agent can be a combination of one or more of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, and lysine diisocyanate.

[0055] S2 specifically includes: adding a polar solvent to the bioenergy material prepolymer to prepare a solution; adding a cross-linking agent to the solution to perform a second chemical reaction, and adding a bone-promoting agent to the system of the second chemical reaction to obtain a mixed solution; placing the mixed solution in a fume hood and stirring it fully, and obtaining a white viscous printing slurry, i.e., a composite slurry, after the polar solvent evaporates. The polar solvent may be a combination of one or more of acetone, hexafluoroisopropanol, and anhydrous ethanol.

[0056] S3, regulating the weight of the osteogenic agent in the composite slurry to obtain three bioenergy material inks containing different weights of the osteogenic agent;

[0057] S4. The three bioenergy material inks containing different weights of osteogenic agents are subjected to gradient 3D printing to respectively simulate the cartilage layer, transition layer and subchondral bone layer in articular cartilage to obtain an osteochondral scaffold with bioenergetic activity.

[0058] In some embodiments, the 3D printing temperature is 60°C to 80°C.

[0059] In the embodiment of the present application, the temperature of 3D printing can be 60°C to 80°C, so that the 3D printing ink can be extruded in a filamentous state, has good continuity, and can be stably formed on the receiving plate. Exemplarily, the temperature of the 3D printing can be 60°C, 65°C, 70°C, 75°C, 80°C, etc.

[0060] In some embodiments, the second chemical reaction system further contains a pore-forming agent.

[0061] In the embodiment of the present application, the system of the second chemical reaction also contains a pore-forming agent, the particle size of which can be 20 μm to 50 μm, and the osteochondral scaffold can be removed by soaking and washing to obtain a multi-level pore structure, that is, a macroporous structure constructed by subsequent 3D printing and a small pore structure formed after the sodium chloride is removed. The multi-level pore structure of this scaffold can promote cell adhesion and retention in the early stage of in vivo implantation, and transport nutrients to promote tissue growth. Exemplarily, the pore-forming agent can be a combination of one or more of sodium chloride, potassium chloride, sodium sulfate, and sugar spheres.

[0062] In some embodiments, the three bioenergy material inks containing different weights of osteogenic agents include: a first bioenergy material ink, a second bioenergy material ink, and a third bioenergy material ink; wherein,

[0063] The first bioenergy material ink satisfies: the weight ratio of the bioenergy material prepolymer to the pore-forming agent is 10:20;

[0064] The second bioenergy material ink satisfies: the weight ratio of the bioenergy material prepolymer, the pore-forming agent and the bone-promoting agent is 10:15.69:1.76;

[0065] The third bioenergy material ink satisfies: the weight ratio of the bioenergy material prepolymer, the pore-forming agent and the bone-promoting agent is 10:9.52:4.29.

[0066] In an embodiment of the present application, the weight of the osteogenic agent in the composite slurry is regulated to obtain three bioenergy material inks containing different weights of osteogenic agents. The first bioenergy material ink (Bioenergetic-active material, BAM) can meet the following requirements: the weight ratio of the bioenergy material prepolymer to the pore-forming agent is 10:20, simulating the cartilage layer in the articular cartilage and promoting the regeneration of hyaline cartilage; the second bioenergy material ink (BAM15) can meet the following requirements: the weight ratio of the bioenergy material prepolymer, the pore-forming agent and the osteogenic agent is 10:15.69:1.76, simulating the transition layer in the articular cartilage, containing 15wt% of the osteogenic agent, and promoting the regeneration of the bone cartilage interface; the third bioenergy material ink (BAM30) can meet the following requirements: the weight ratio of the bioenergy material prepolymer, the pore-forming agent and the osteogenic agent is 10:9.52:4.29, simulating the lower bone layer of the articular cartilage, containing 30wt% of the osteogenic agent, and promoting the rapid reconstruction of the subchondral bone.

[0067] S4 is as follows: three types of printing inks are loaded into the 3D printing cylinder respectively. The temperature of the printing cylinder can be set to 60℃~80℃ according to the extrusion conditions, so that the 3D printing ink can be extruded in a filamentous state with good continuity and can be stably formed on the receiving plate. The print head is selected to be 0.4mm, the layer height is set to 0.31mm, and the printing spacing is 1.0mm. First print 4 layers of BAM30, switch to BAM15 ink to print 4 layers, and finally switch to BAM ink to print 2 layers to obtain the osteochondral scaffold.

[0068] In some embodiments, the method further comprises: S5, subjecting the osteochondral scaffold to a third chemical reaction to obtain a target osteochondral scaffold.

[0069] In the embodiment of the present application, the osteochondral scaffold is subjected to a third chemical reaction (secondary cross-linking) to obtain a target osteochondral scaffold, which can make the remaining hydroxyl and carboxyl groups in the osteochondral scaffold system undergo esterification reaction to form a polymer network, and the scaffold is stably formed, has a certain strength, and will not disintegrate in water; the cartilage layer, transition layer, and subchondral bone layer use the same base material (bioenergy active material) to fully cross-link to form a tight interlayer bonding layer; the molecular cross-linking density can be adjusted by regulating the cross-linking time, and then the degradation rate of the scaffold can be regulated to meet the balance requirements of tissue growth and scaffold degradation. Therefore, the osteochondral scaffold after 3D printing is subjected to a third chemical reaction to obtain a stable three-dimensional scaffold, and then the sodium chloride is fully removed in deionized water, and finally a three-dimensional bioenergy active scaffold (BG-BAM) with a multi-level pore structure is obtained. In the third chemical reaction, the temperature can be 120℃~160℃, and the time can be 24h~48h, which can make the scaffold molding stable and have a certain strength; the scaffold interlayer is tightly bonded; the molecular cross-linking density can be adjusted by regulating the cross-linking time, thereby regulating the degradation rate of the scaffold, and then the degradable osteochondral scaffold with matching tissue regeneration speed can be customized according to the size of the defect. The scaffold accelerates tissue regeneration by regulating cell energy metabolism, without pre-setting growth factors and seed cells, and has the characteristics of safety, controllability and high efficiency. In addition, it can be carried out in a vacuum of -100KPa. Exemplarily, the temperature can be 120℃, 130℃, 140℃, 150℃, 160℃, etc.; the time can be 24h, 28h, 32h, 36h, 40h, 44h, 48h, etc.

[0070] The present application provides a method for preparing a bone cartilage scaffold with bioenergetic activity, which has the following advantages:

[0071] (1) Bone cartilage scaffolds can produce bioenergy active units during the degradation process. These active units can be absorbed by cells and used to enter the mitochondrial tricarboxylic acid cycle, thereby increasing the speed of the tricarboxylic acid cycle by establishing a key intermediate biological bypass. Since the tricarboxylic acid cycle is an important metabolic pathway for the production of adenosine triphosphate (ATP), accelerating the cycle speed can increase the amount of ATP produced in cells, providing sufficient energy for various life activities of cells, such as cell proliferation, differentiation, and synthesis of extracellular matrix, thereby accelerating tissue regeneration through energy supply, fundamentally helping the repair and reconstruction of bone cartilage tissue;

[0072] (2) The high molecular weight polymer synthesized from the intermediate of the tricarboxylic acid cycle and triol is used as the basic material for constructing tissue engineering scaffolds, and then combined with ingredients such as bone-promoting agents, so that the scaffold can not only provide support for tissue repair from the perspective of energy metabolism, but also have the direct function of promoting bone formation. At the same time, through 3D printing, it simulates the natural tissue hierarchy, and has good performance in many aspects such as structure, function and adaptability to the biological environment. It is expected to play an important role in the field of osteochondral injury repair;

[0073] (3) The bio-ink contains a pore-forming agent, which is removed by soaking and washing after the scaffold is formed to obtain a multi-level pore structure, namely, a macroporous structure constructed by 3D printing and a microporous structure formed after the sodium chloride is removed. The multi-level pore structure of the scaffold can promote cell adhesion and retention in the early stage of implantation in the body, and transport nutrients to promote tissue growth;

[0074] (4) Based on the tissue composition and structural characteristics of the osteochondral unit, bioenergy ink containing different weights of osteogenic agents was used to print layer by layer to obtain an integrated scaffold with a gradient change of hydroxyapatite. This bionic osteochondral integrated scaffold can effectively promote the migration, growth and differentiation of host cells during the tissue repair process;

[0075] (5) After 3D printing, the osteochondral scaffold undergoes secondary thermal cross-linking to achieve close bonding between layers, preventing it from cracking and stratifying during tissue repair, thus ensuring high-quality repair of the osteochondral interface.

[0076] In a second aspect, an embodiment of the present application provides a bone cartilage scaffold with bioenergetic activity, wherein the bone cartilage scaffold is prepared by the method described in any one of the embodiments of the first aspect.

[0077] In the embodiment of the present application, the osteochondral scaffold has bioenergetic activity, so that the osteochondral scaffold achieves hyaline cartilage regeneration and reconstruction of the complex interface of osteochondral.

[0078] The osteochondral scaffold is realized based on the preparation method of the above-mentioned osteochondral scaffold. The specific steps of the preparation method of the osteochondral scaffold can refer to the above-mentioned embodiment. Since the osteochondral scaffold adopts part or all of the technical solutions of the above-mentioned embodiment, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be repeated here one by one.

[0079] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for the unrecorded specific conditions in the following examples are usually measured according to national standards. If there is no corresponding national standard, then carry out according to general international standards, normal conditions or according to the conditions recommended by the manufacturer.

[0080] Example 1

[0081] A method for preparing a bone cartilage scaffold with bioenergetic activity, comprising:

[0082] Under stirring, succinic acid and glycerol, intermediates of the tricarboxylic acid cycle, in equal amounts are mixed in a three-necked flask and placed in an oil bath at 150°C. After the two monomers are completely mixed, the vacuum degree is -80KPa, and stirring is continued for 5 hours to obtain a bioenergy material prepolymer;

[0083] The bioenergy material prepolymer and acetone are prepared into a solution, hexamethylene isocyanate, hydroxyapatite (HA) and sodium chloride are sequentially added into the solution to form a mixed solution, and the mixed solution is placed in a fume hood and fully stirred until the acetone is completely evaporated to obtain a composite slurry;

[0084] The weight of hydroxyapatite in the composite slurry was adjusted to obtain three bioenergy material inks containing different weights of osteogenic agents (see Table 1);

[0085] Three bioenergetic material inks containing different weights of osteogenic agents were used for gradient 3D printing to simulate the cartilage layer, transition layer and subchondral bone layer in articular cartilage, respectively, to obtain osteochondral scaffolds; specifically, the three printing inks were respectively filled in the 3D printing cylinder, the printing cylinder temperature could be set to 65°C according to the extrusion situation, the print head was selected to be 0.4mm, the layer height was set to 0.31mm, and the printing spacing was 1.0mm. First, 4 layers of BAMHA30 were printed, then 4 layers were printed with BAMHA15 ink, and finally 2 layers were printed with BAM ink, to obtain a biomimetic gradient bioenergetic-active scaffold (BG-BAM).

[0086] The osteochondral scaffold is subjected to secondary cross-linking molding to obtain the target osteochondral scaffold. The process parameters of the secondary cross-linking molding include: temperature 150°C, vacuum -100KPa, and time 24h.

[0087] Table 1 Three bioenergetic material inks containing different weights of osteogenic agents

[0088] Bio-energy printing ink Prepolymer mass (g) Sodium chloride (g) Hydroxyapatite(g) BAM 10 20 0 BAMHA15 10 15.69 1.76 BAMHA30 10 9.52 4.29

[0089] Comparative Example 1

[0090] The polycaprolactone (PCL) material approved by the U.S. Food and Drug Administration (FDA) was used as the base material and dissolved in chloroform. A certain amount of HA was added and stirred thoroughly. After the solvent evaporated, three PCL inks with different HA weights were obtained (as shown in Table 2 below). The three printing inks were filled in the 3D printing cylinder respectively. The printing cylinder temperature can be set to 90°C according to the extrusion situation, the print head is selected to be 0.4mm, the layer height is set to 0.31mm, and the printing spacing is 1.0mm. First print 4 layers of PCLHA30, switch to PCLHA15 ink to print 4 layers, and finally switch to PCL ink to print 2 layers to obtain the biomimetic gradient PCL scaffold (Biomimetic gradient PCLscaffold, BG-PCL).

[0091] Table 2 PCL inks with three different HA weights

[0092] PCL Printing Ink Prepolymer mass (g) Hydroxyapatite(g) PCL 10 0 PCLHA15 10 1.76 PCLHA30 10 4.29

[0093] Analysis of Example 1 and Comparative Example 1:

[0094] 1) Due to the high molecular weight of PCL, even if sodium chloride is fully ground to 20-50um, it still cannot be evenly dispersed in PCL, and obvious separation occurs after the solvent evaporates. BAM has a low molecular weight and can be fully mixed with sodium chloride powder to construct a multi-level porous structure through the sacrificial template method; 2) BAM can achieve tight fusion between layers through two cross-linking, and the second cross-linking density can be artificially controlled to adjust the degradation rate of the scaffold. PCL is formed in one step by hot melt condensation, and the layers are prone to loose fusion, and layer separation occurs during the repair process.

[0095] Characterization of the osteochondral scaffolds prepared in Example 1 and Comparative Example 1

[0096] 1) Characterization of bioenergetic activity of bioenergetic materials

[0097] Figure 2 The JC-1 staining results of cells treated with the test medium provided in the examples of the present application, CCCP is used as a positive control for inducing a decrease in mitochondrial membrane potential; Figure 3The results of the mitochondrial membrane potential change and ATP activity test of the cells treated with the test medium provided in the examples of the present application; see Figures 2-3 , bioenergetic active scaffolds (BAM), bioenergetic active material composite apatite scaffolds (BAMHA) and PCL scaffolds were prepared by 3D printing, and the degradation products (DP) of the three scaffolds were added to the growth medium to obtain test medium (PCL-DP, BAM-DP and BAMHA-DP) for cell culture. Mitochondrial membrane potential detection kit (JC-1, Figure 2 ) The test results showed that BAM-DP and BAMHA-DP could significantly increase the mitochondrial membrane potential, which was significantly higher than that of Blank and PCL-DP groups ( Figure 3 A). By testing the ATP activity of cells, it was found that the BAM-DP and BAMHA-DP groups significantly promoted the ATP production of cells ( Figure 3 B).

[0098] 2) Characterization of scaffold structure and element distribution

[0099] Figure 4 The physical image, SEM image and element distribution spectrum of the osteochondrocyte scaffold with bioenergetic activity provided in the embodiments of the present application; please refer to Figure 4 The SEM image of the biomimetic gradient bone cartilage scaffold with bioenergetic activity (BG-BAM) shows that the scaffold has a 3D printed macroporous structure with a pore size of 500 μm. The enlarged cross-sectional view of the scaffold shows a microporous structure of 20-50 μm, which is conducive to cell adhesion and retention, as well as nutrient transport ( Figure 4 A). From the microstructure of different layers, we can see the gradually increasing mineral-like materials, which are hydroxyapatite biological components. The energy spectrum analysis also clearly reflects the distribution of calcium (Ca) elements, which gradually increases from top to bottom ( Figure 4 B).

[0100] 3) Characterization of scaffold interlayer bonding

[0101] Figure 5 Interlaminar scanning electron microscopy images of the bioenergetic active bone cartilage scaffold (BG-BAM) and PCL bone cartilage scaffold (BG-PCL) provided in the embodiments of the present application; see Figure 5 , the layers of the osteochondral scaffold with bioenergetic activity were tightly bound, while the layers of the PCL osteochondral scaffold were obviously separated.

[0102] Example 1: A bone cartilage scaffold (BG-BAM) with bioenergetic activity was prepared and applied to repair bone cartilage defects:

[0103] Figure 6The osteochondral scaffold with bioenergetic activity provided in the embodiment of the present application is applied to the osteochondral defect repair surgery repair diagram; please refer to Figure 6 , at 12 weeks, the defect surface of the bioenergetically active osteochondral scaffold (BG-BAM) group regenerated cartilage with the same color as the surrounding cartilage.

[0104] Figure 7 The histological staining results of the osteochondral scaffold with bioenergetic activity provided in the embodiment of the present application after 12 weeks of osteochondral defect repair surgery; please refer to Figure 7 ; At 12 weeks, the results of hematoxylin and eosin (H&E) and safranin fast green (SF) staining showed that the defect surface of the bone cartilage scaffold (BG-BAM) group regenerated a cartilage layer (newcartilage, NC), the interface between cartilage and subchondral bone was clear and complete, and the new subchondral bone (new bone, NB) had a structure similar to the surrounding bone tissue. Immunohistochemical staining of cartilage-specific protein (COLII) showed that the generated cartilage was rich in type II collagen and typical chondrocyte arrangement. Immunohistochemical staining of bone-specific protein (COL I) showed that high-quality subchondral bone was reconstructed. In summary, the bone cartilage scaffold with bioenergetic activity regenerated hyaline cartilage and reconstructed the bone cartilage interface.

[0105] One or more technical solutions in the embodiments of the present application also have at least the following technical effects or advantages:

[0106] (1) In the present embodiment, bioenergy active materials are selected as the substrate, hydroxyapatite is fully mixed to prepare a bioenergy material-hydroxyapatite composite bio-ink, and then a three-dimensional porous scaffold is constructed by 3D printing, which can accelerate tissue regeneration by improving the cell energy state and significantly promote bone cartilage regeneration;

[0107] (2) The osteochondrocyte scaffold with bioenergetic activity provided in the embodiments of the present application has a multi-level pore structure, which is conducive to cell residence and adhesion, nutrient transport and tissue ingrowth;

[0108] (3) The bioenergetically active osteochondral scaffold has a biomimetic structure and composition, with tight interlayer bonding, ensuring high-quality regeneration of the osteochondral interface;

[0109] (4) The osteochondral scaffold with bioenergetic activity has an adjustable degradation rate, which can promote osteochondral regeneration safely, controllably and efficiently.

[0110] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features applied for herein.

Claims

1. A method for preparing a bone cartilage scaffold having bioenergetic activity, the method comprising: The intermediate of tricarboxylic acid cycle is subjected to a first chemical reaction with triol to obtain a bioenergy material prepolymer; The bioenergy material prepolymer and the cross-linking agent are subjected to a second chemical reaction, and a bone formation promoting agent is added to the system of the second chemical reaction to obtain a composite slurry; Regulating the weight of the osteogenic agent in the composite slurry to obtain three bioenergy material inks containing different weights of the osteogenic agent; The three bioenergy material inks containing different weights of osteogenic agents are subjected to gradient 3D printing to respectively simulate the cartilage layer, transition layer and subchondral bone layer in articular cartilage to obtain an osteochondral scaffold with bioenergetic activity.

2. The method according to claim 1, characterized in that The intermediates of the tricarboxylic acid cycle include at least one of the following: citric acid, α-ketoglutaric acid, succinic acid, fumaric acid, malic acid, oxaloacetic acid; and / or, The triol includes at least one of the following: glycerol, butanetriol, hexanetriol, and decantriol.

3. The method according to claim 1, characterized in that The molar ratio of the intermediate of the tricarboxylic acid cycle to the triol is (1-3):1; and / or, The temperature of the first chemical reaction is 120°C to 160°C.

4. The method according to claim 1, characterized in that: The bone formation promoting agent includes one of the following: hydroxyapatite, tricalcium phosphate, and bioactive glass.

5. The method according to claim 1, characterized in that The cross-linking agent includes at least one of the following: toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, and lysine diisocyanate.

6. The method according to claim 1, characterized in that The temperature of the 3D printing is 60°C to 80°C.

7. The method according to claim 1, characterized in that The second chemical reaction system further contains a pore former.

8. The method according to claim 7, characterized in that The three bioenergy material inks containing different weights of bone-promoting agents include: a first bioenergy material ink, a second bioenergy material ink and a third bioenergy material ink; wherein, The first bioenergy material ink satisfies: the weight ratio of the bioenergy material prepolymer to the pore-forming agent is 10:20; The second bioenergy material ink satisfies: the weight ratio of the bioenergy material prepolymer, the pore-forming agent and the bone-promoting agent is 10:15.69:1.76; The third bioenergy material ink satisfies: the weight ratio of the bioenergy material prepolymer, the pore-forming agent and the bone-promoting agent is 10:9.52:4.

29.

9. The method according to claim 1, characterized in that: The method further comprises: The osteochondral scaffold is subjected to a third chemical reaction to obtain a target osteochondral scaffold; wherein the process parameters of the third chemical reaction include: a temperature of 120° C. to 160° C. and a time of 24 h to 48 h.

10. An osteochondral scaffold with bioenergetic activity, wherein the osteochondral scaffold is prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A graded active scaffold material for osteocartilage repair, its preparation method and application

    CN102274548A

  • Three-dimensional scaffold with biological energy activity and preparation method thereof

    CN119119412A

  • Polymer-ceramic-hydrogel composite scaffold for osteochondral repair

    US20060036331A1